Resistensi Kaum Tertindas terhadap Otoritarianisme dalam Novel Jumhuriyyatu Ka'anna Karya Alaa Al-Aswany: Analisis Teori James C. Scott - Ismail Syah Razi Al-Faruq; Fadlil Yani Ainusyamsi; Mohamad Syasi (Dzil Majaz: Journal of Arabic Literature, 2026)
Authoritarian oppression often silences freedom, yet simultaneously triggers resistance tactics from the oppressed. This dynamic is depicted in Alaa Al-Aswany’s novel Jumhuriyyatu Ka’anna, set during the 2011 Egyptian Revolution. This descriptive qualitative research aims to analyze the forms of open and closed resistance, along with their underlying factors, using a sociology of literature approach and James C. Scott's theory. Results indicate that open resistance manifests through demonstrations, labor strikes, verbal confrontations, visual campaigns, institutional disobedience, and physical resistance. Meanwhile, closed resistance is executed covertly through false compliance, sabotage, evasion, safe space creation, disguise, and withdrawal from the system. These resistances are driven by extreme human rights violations, formal justice system failures, and economic exploitation. The scientific contribution of this study lies in recontextualizing Scott's theory from traditional agrarian societies to a modern urban landscape, revealing novel resistance tactics through the use of visual technology and religious attributes. In conclusion, authoritarian hegemony is never absolute, as the subordinate class consistently finds ways to nurture resistance.